1976
DOI: 10.1210/endo-99-1-125
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Function and Insulin Secretion from the Perfused Pancreas in the Rat

Abstract: The influence of thyroid function on the kinetics of glucose-induced insulin secretion from the isolated perfused rat pancreas has been studied. L-Thyroxine (L-T4) administration did not modify the immediate insulin secretory response of the perfused pancreas to glucose. L-Triiodothyronine (L-T3) treatment as well as propylthiouracil (PTU) treatment decreased the immediate insulin secretory response of the pancreas slightly. Only thyroidectomy (Tx) reduced the immediate secretory response of the pancreas signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
1
2

Year Published

1976
1976
2010
2010

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 0 publications
0
20
1
2
Order By: Relevance
“…Experimental hyperthyroidism induced by thyroid hormone treatment leads to a reduction in glucoseinduced insulin secretion from the isolated pancreas (31), and this is not due to impairment of the insulin-secreting capacity of individual ␤-cells (32). It was also reported that stimulated insulin secretion is significantly increased in patients with hyperthyroidism, possibly reflecting increased ␤-cell sensitivity to glucose (33).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental hyperthyroidism induced by thyroid hormone treatment leads to a reduction in glucoseinduced insulin secretion from the isolated pancreas (31), and this is not due to impairment of the insulin-secreting capacity of individual ␤-cells (32). It was also reported that stimulated insulin secretion is significantly increased in patients with hyperthyroidism, possibly reflecting increased ␤-cell sensitivity to glucose (33).…”
Section: Discussionmentioning
confidence: 99%
“…In particularly prone individuals, hyperthyroidism can induce a so-called "thyroid diabetes" [2]. Thyroxine treatment causes a state of experimental hyperthyroidism and reduces the pancreatic insulin content and glucose-induced insulin secretion [4,5]. This is accompanied by a reduction in the beta-cell volume of the pancreas [5].…”
Section: Methodsmentioning
confidence: 99%
“…given i.p. for 5 consecutive days) (Sigma, St. Louis, Mo., USA) dissolved in 0.9% NaCl solution [4,9]. Alternatively, in time course studies, L-thyroxine (20 mg/kg b.wt.)…”
Section: Methodsmentioning
confidence: 99%
“…The findings in the present work suggest that glucose possesses the highest capacity to stimulate insulin secretion from the pancreas of hypothyroid animals whereas this capacity is minimum in the hyperthyroid rats. Charles et al (1975) showed that glucose elevates the cyclic AMP level in the beta cells which acts as a feed forward modulator of glucose induced insulin release in euthyroid animals, while Lenzen et al (1976) suggested that hyperthyroidism results in decreased glucose induced insulin release, whereas experimental hypothyroidism induces increased secretion of insulin from the pancreas. On the contrary, Balabokin (1971) and Jolin (1974) found that in hypothyroidism glucose-induced insulin secretion decreases but thyroxine treatment reverses the effect.…”
mentioning
confidence: 99%